Antenatal Care Description and Pregnancy Risk of Pregnancy in Pregnant Mother in Palu City 2019: Study of Co-Ass Assistance for IKM-KK Faculty of Medicine, Tadulako University - Ketut Suarayasa; Bertin Ayu Wandira (Newinera Publisher, 2020)
The purpose of this study was to obtain an overview of pregnancy risk factors in pregnant women accompanied by young doctor from the IKM-KK department of the Faculty of Medicine at Tadulako University during a stase at the Primary Health Care in the city of Palu. The design of this study was descriptive in order to obtain an overview of pregnancy risk factors obtained from the checklist for assisting pregnant women. The population in this study were all pregnant women who received young doctor from the IKM-KK department in the last 2 (two) years, totaling 147 pregnant women. While the sample in this study was 3rd trimester pregnant women whose notes in the accompanying book are complete. The results showed that: 1) Compliance with the lowest Antenatal Care standard in laboratory tests (70%); 2) Pregnant Women with Low Risk Pregnancy (KRR) of 58.2%, High Risk Pregnancy (KRT) of 32.2% and Very High Risk Pregnancy (KRST) of 9.6%; 3) The three highest risk factors for pregnancy are getting pregnant too soon again <2 years (31.3%), had cesarean section (22.9%) and pre-eclampsia (16.7%); and 4) Pregnant women with very high risk pregnancies (KRST) at most (72.7%) were found in urban health centers, including: kamonji (36.3%), Singgani (18.2%) and Talise (18.2%).